Sustainability in the digitally optimised maritime industry - Kruger, Katri (My University, 2021)
The increasing volumes in global maritime trade are associated with accumulating stresses and adverse effects on the environment. Measures such as stricter regulations and renewed legislation are implemented to pivot the industry towards global sustainable development goals. While the end goal of achieving carbon neutrality remains problematic and slow-going, several short-term solutions could be found. This study aims to explore how digitalisation can support the sustainable development of the maritime industry, focusing primarily on enhancing port efficiency. The purpose of the study is divided into two sub-questions: what are the sustainability impacts of the maritime industry, and how could digitalising port calls impact shipping emissions? The study's theoretical framework consists of three large concepts; sustainability, digital transformation, and the maritime industry's complexity, particularly the port operations, are discussed. The research method used in this study is quantitative, as the research problem is best addressed by processing numerical data. The results of the study are in line with previous research, indicating that optimising the port operations and reducing waiting time could have significant impacts on CO2 emissions. Lowering the CO2 emissions leads to the sustainable development of the environment and economic and social sustainability as the cost savings have the potential to reach billions of USD and have positive effects on social well-being. While change on a global scale may not be viable to implement due to development maturity, more realistic scenarios, such as a change in top 30 GDP countries, depict the ability to implement digitalisation and JIT shipping effectively and at scale. By leveraging their current infrastructure and economic capabilities, these countries alone could produce significant sustainability impacts while remaining competitive. To tackle the global issue of climate change, the decision-makers should thus invest and incentivise the maritime actors to optimise their operations that directly lead to the industry's sustainable development.

Maailman meriteollisuuden kasvuun liittyy lisääntyviä stressitekijötä ja haitallisia ympäristövaikutuksia. Toimenpiteitä, kuten tiukempia määräyksiä ja uudistettua lainsäädäntöä, toteutetaan, jotta ala saataisiin kohti globaaleja kestävän kehityksen tavoitteita. Vaikka lopullinen tavoite hiilineutraaliuden saavuttamiseksi on edelleen ongelmallinen ja hidas saavuttaa, voidaan useita lyhyen aikavälin ratkaisuja ottaa käyt-töön. Tämän tutkimuksen tarkoituksena on selvittää, miten digitalisaatio voi tukea mer-iteollisuuden kestävää kehitystä keskittymällä ensisijaisesti satamatehokkuuden paran-tamiseen. Tutkimuksen tarkoitus on jaettu kahteen alakysymykseen: mitkä ovat meren-kulkualan kestävän kehityksen vaikutukset ja miten satamatoimintojen digitalisointi voi-si vaikuttaa merenkulun päästöihin? Tutkimuksen teoreettinen kehys koostuu kolmesta suuresta käsitteestä; kestävästä kehityksestä, digitaalisesta muutoksesta ja merenkulkualan, erityisesti satamatoimintojen monimutkaisuudesta. Tutkimusmenetelmänä käytetään kvantitatiivista menetelmää, sillä tutkimusongelmaan voidaan parhaiten pureutua analysoimalla numeerista dataa. Tutkimuksen tulokset ovat aiempien tutkimusten mukaisia, ja ne osoittavat, että sa-tamatoimintojen optimoinnilla ja odotusajan lyhentämisellä voi olla merkittäviä vaikutuksia hiilidioksidipäästöihin. Hiilidioksidipäästöjen vähentäminen johtaa ympäristön kestävään kehitykseen sekä taloudelliseen ja sosiaaliseen kestävyyteen, sillä kustannussäästöt voivat saavuttaa miljardeja dollareita ja vaikuttaa myönteisesti so-siaaliseen hyvinvointiin. Vaikka globaalin mittakaavan muutos ei välttämättä ole toteut-tamiskelpoinen sen kehityksen kypsyyden vuoksi, realistisemmat skenaariot, kuten muutos 30 parhaan BKT-maan joukossa, kuvaavat kykyä toteuttaa digitalisaatio ja just-in-time (juuri ajoissa) tehokkaasti ja laajamittaisesti. Hyödyntämällä nykyistä infra-struktuuriaan ja taloudellisia valmiuksiaan nämä maat yksin voivat tuottaa merkittäviä kestävyysvaikutuksia pysyen kilpailukykyisinä. Ilmastonmuutoksen maailmanlaajuisen ongelman ratkaisemiseksi päätöksentekijöiden olisi siten investoitava ja kannustettava merenkulun toimijoita optimoimaan toimintaansa, mikä johtaa suoraan alan kestävään kehitykseen.
Keywords: Sustainability, maritime industry, digitalisation, Just-in-Time